EIN3 and PIF3 Form an Interdependent Module That Represses Chloroplast Development in Buried Seedlings. Issue 12 (7th November 2017) - Liu, Xiaoqin; Liu, Renlu; Li, Yue; Shen, Xing; Zhong, Shangwei; Shi, Hui
Abstract : The EIN3-PIF3 pair functions as a central integrator of multiple signals for the concerted repression of chloroplast development in soil. Abstract: In buried seedlings, chloroplasts are arrested at the etioplast stage, but they rapidly mature upon emergence of the seedling. Etioplast-chloroplast differentiation is halted through the integration of soil-induced signals, including pressure and the absence of light, although the details on how this information converges to regulate cellular decisions remain unclear. Here, we identify an interdependent transcription module that integrates the mechanical pressure and darkness signals to control chloroplast development in Arabidopsis thaliana . Mutations of ETHYLENE-INSENSITIVE3 (EIN3), the primary transcription factor in the ethylene signaling pathway that is activated in response to mechanical pressure, cause early development of etioplasts in the dark and severe photobleaching upon light exposure. Genetic studies demonstrate that repression of etioplast differentiation by EIN3 requires PHYTOCHROME INTERACTING FACTOR3 (PIF3), a darkness-stabilized bHLH transcription factor. EIN3 and PIF3 directly interact and form an interdependent module to repress the expression of most LIGHT HARVESTING COMPLEX ( LHC ) genes; overexpressing even one LHC could cause premature development of etioplasts. The EIN3-PIF3 transcription module synergistically halts chloroplast development by interdependently co-occupying the promoters of LHC genes. Thus, our results define a transcriptional regulatory module and provide mechanistic insight on the concerted regulation of chloroplast development by multiple soil-induced signals.